The association between oral microbiome and gastric precancerous lesions - Yifei Chen; Lei Lei; Mengying Xia; Ran Cheng; He Cai; Tao Hu (mSystems)
ABSTRACT Gastric precancerous lesions are thought to be precursors in the occurrence and development of gastric cancer through Correa's cascade. Recent studies have investigated the association between the oral microbiome and gastric precancerous lesions. However, there has yet to be a comprehensive synthesis review of the existing literature on the relationship between oral microbiome and gastric precancerous lesions. A systematic review was conducted to characterize the literature on the association between oral microbiome and gastric precancerous lesions. The studies show that oral microbiome is dynamic in individuals with gastric precancerous lesions. Oral-derived microorganisms were colonized in the gastric precancerous lesions. Interactions between oral and gastric microbiomes affect the response of the host immunity. The abnormal proliferation of oral-associated microorganisms may be linked to the reduction of gastric acid. The present review supports the potential association between oral microbiome and gastric precancerous lesions. However, the interactions are complex and multifaceted, which require further investigation.